A (re) escritura do texto nas aulas de língua portuguesa: implicações para o processo de aprendizado - Aguiar neta, Maria do Carmo Melo (2015)
There are studies about reading and writing, as well as official documents that rule the Basic Education in Brazil, which emphasize the importance of working these skills in classroom, in order to guarantee to the students/subjects the full exercise of citizenship. This way, the role of school must be to foment the writing production of its students, enlarging the communicative competence of them, in accordance to the National Curricular Parameters of the Portuguese Language (1998). In this perspective, the work with didactic sequences, according to the model presented by Dolz, Noverraz and Scheneuwly (2004), is showed as very promising because, by means of teaching modules, it is possible to work, punctually, the difficulties presented by the students by occasion of the initial production of the textual genre under study. On the above, the present research aims to evaluate the contributions of using of a didactic sequence, from the news genre, in the process of writing production of students of the seventh grade of Elementary School in a public school in Santa Rita/PB, situated in the metropolitan region of João Pessoa. In addition, it is a qualitative and interventionist research. Based on the conception of genre (BAKHTIN, 2011), as well as on the contributions of researchers, such as: Bezerra (2010), Dolz (2004), Marcuschi (2008, 2010), Noverraz (2004), Schneuwly (2004), all related to this theme, the application of this procedure was developed by the observation of the interactional aspects mobilized by the students who participated of the research to achieve their communicative objectives. Furthermore, the present research also aimed to observe the effects of this didactic sequence in the writing production of these subjects, in order to enable them to develop skills that transcend the studied genre and that could be transferred by other textual genres which belong to the same discursive domain. It is important to emphasize that the writing production tasks of the textual genre were prepared to a real objective of interaction and not only as a writing task in school ambit. The presented results demonstrate that a writing task based on the quotidian of students can be enlarged from a known textual genre. This way, it is achieved the improvement of discursive skills and it also stimulates a bigger interest by the involved subjects in the process.